Theory of imperfect information: implications of economic policy. Conference at Universidad Andina Simón Bolívar, Sede Ecuador, in the delivery of the Doctorate Honoris Causa - Stiglitz, Joseph (2016)
In this talk, Joseph Stiglitz presents a scheme of his theory on imperfect information, and its implications on economic theory. In this presentation, he questions several economic premises, and argues that market failures occur every time information is imperfect or markets are in-complete. Stiglitz's theory of imperfect information underscores the economic ideas generally known as the "Washington consensus': ideas he thinks come from a market fundamentalist view.